Blake's humanism - Beer, John (Humanities-Ebooks, 2007)
An illustrated study of the social, political and literary thought underlying Blake's Songs and the Prophetic Books, culminating in Milton. It considers the guiding forces behind Visions of the Daughters of Albion and The Marriage of Heaven and Hell, the roles of vision and energy in the Songs of Innocence and of Experience and lyrics such as 'The Mental Traveller' Blake's attempts at mythological interpretation of current events, first in 'The French Revolution' and then in the prophetic books America, Europe and The Song of Los, and how Blake's fourfold vision is employed as a means of interpreting and illustrating major predecessors such as Milton and Chaucer.